Mechanical and Thermal Properties of Polymethyl Methacrylate-BN Nanotube Composites. (21st December 2008) - Zhi, C. Y.; Bando, Yoshio; Wang, Wenlong L.; Tang, Chengchun C.; Kuwahara, Hiroaki; Golberg, Dmitri
Abstract : Polymethyl methacrylate (PMMA)-BN nanotube (BNNT) composites were fabricated and their mechanical and thermal properties were analyzed. Using a 1 wt.% BNNTs fraction in a polymer, the elastic modulus of PMMA was increased up to 19%. In addition, thermal stability and glass transition temperature of PMMA were also positively affected. The thermal conductivity of PMMA with BNNT additions increased three times. The resultant BNNT-PMMA composites possess the high electrical breakover voltages. Thus our studies clearly indicate that BNNTs are promising nanofillers for improvement of mechanical and thermal conductivity of dielectric polymers under preservation of their electrical insulation.